2021
DOI: 10.1002/pamm.202000305
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Particle Finite Element Method (A‐PFEM) in Metal Cutting Processes

Abstract: Machining is very common in industry, e.g. automotive industry and aerospace industry, which is a nonlinear dynamic problem including large deformations, large strain, large strain rates and high temperatures, that implies some difficulties for numerical methods such as Finite element method. One way to simulate such kind of problems is the Particle Finite Element Method (PFEM) which combines the advantages of continuum mechanics and discrete modeling techniques. In this work we introduce an improved PFEM call… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…[8] FEM can deliver powerful solutions to the field of cutting research, as it is capable of visualizing details such as chip deformation and breaking, stress fields, force changes, heat distribution, the shape of the machined surface, and so on. [9][10][11] In previous studies, chip deformation in AISI 4340 steel was simulated and the von Mises stress was analyzed by Guo and Yen [12] through the use of FEM. This work showed that shearing plays an important role when discontinuous chips are released during machining.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] FEM can deliver powerful solutions to the field of cutting research, as it is capable of visualizing details such as chip deformation and breaking, stress fields, force changes, heat distribution, the shape of the machined surface, and so on. [9][10][11] In previous studies, chip deformation in AISI 4340 steel was simulated and the von Mises stress was analyzed by Guo and Yen [12] through the use of FEM. This work showed that shearing plays an important role when discontinuous chips are released during machining.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 ] FEM can deliver powerful solutions to the field of cutting research, as it is capable of visualizing details such as chip deformation and breaking, stress fields, force changes, heat distribution, the shape of the machined surface, and so on. [ 9–11 ]…”
Section: Introductionmentioning
confidence: 99%